Extractive Imperialism in the Americas : Capitalism's New Frontier. - Petras, James F., 1937- (Studies in critical social sciences., 2014)
This book explores the changing face of US imperialism in the context of a system that is in crisis. At issue are the devastating effects of the turn of many multinational corporations towards 'extractivism'-a pillage of society's natural resources.